Power Transformer Wire Estimate (Asian Education Studies, 2017)
This experimental study determined the weight of wire used in power supply using the laboratory technique and procedure to gather data. There were two designs with three treatments each, prepared and subjected to using the Two Way Analysis of Variance. The treatments for the first design were: one is 1 1/8 inch by 1 1/8 inch area and output voltage of 6 volts; two is 1 1/8 inch by 1 1/8 inch area and output voltage of 36 volts; three is 1 1/8 inch by 1 1/8 inch area and output voltage of 110 volts. The treatments for design number two were: one is 1/2 inch by 1/2 inch area and output voltage of 12 volts; two is 3/4 inch by 3/4 inch area and output voltage of 12 volts; three is 1 inch by 1 inch area and output voltage of 12 volts. The test result of significant differences in the effectiveness, efficiency and performance of the different treatments showed no significant difference on windings, temperature, voltage, size of the iron core, current, power, number of turns, turns per volt and force applied in winding.